Positive Leadership and its Impact on Improving the Climate in Chilean Schools. A Comparison between Teachers and School Leaders - Lacourt Suárez, Luis (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2026)
This article analyzes the opinions of teachers and principals regarding relationships and the presence (or absence) of relational trust and positive leadership in Chilean public schools in the Metropolitan and O’Higgins regions. The development of positive school climates, where respect and relational trust are key factors in promoting improvement strategies, aligns with coexistence, democracy, and equity. Leaders’ actions are central to this, making resilience and relational trust key professional competencies, especially in complex and disadvantaged contexts. The study employs a mixed-methods, procedural design, combining a Google Forms questionnaire, validated by experts, to obtain an overview of the topic (with 95 responses), and six in-depth interviews with three principals to contextualize and understand the scope and meaning of the data. The results indicate that relational trust impacts the work climate, emotional well-being, teamwork, and the achievement of institutional goals. This highlights the importance of training in active listening, the development of multilevel relational trust, and democratic decision-making. In turn, leaders and teachers must be competent in interpersonal skills, perceiving the needs of the community. Furthermore, the following emerge: A demand for initial and ongoing teacher training in the development of interpersonal skills; and the importance of interpersonal relationships and trust as professional competencies. At the same time, it concludes that schools must create spaces of care, safety, and interaction as a necessary condition for generating spaces for dialogue and mutual institutional reciprocity. This is relevant for achieving a shared vision and purpose for improving outcomes for all members of the educational community.